Clinical cardiac electrophysiology : techniques and interpretations - Josephson, Mark E (Lippincott Williams & Wilkins, 2002)
Harvard Medical School, Boston, MA. Provides the novice electrophysiologist with an electrophysiologic approach to arrhythmias, which is predicated on the hypothesis that a better understanding of the mechanisms of arrhythmias will lead to more successful and rationally chosen therapy. Stresses methodology required to define the mechanism. Previous edition: c1993.
Keywords: elektrokardiografie; Electrocardiography; DIAGNÓZA KARDOIOVASKULÁRNÍ; fyziologie; radiologie, nukleární medicína a zobrazovací metody; Heart Diseases; kardiologie; srdeční arytmie; Arrhythmias, Cardiac; nemoci srdce